Manifestation of Social Constructionism in the Process of Teaching and Learning - Vaičiūnienė, Asta; Kazlauskienė, Aušra (Technium Social Sciences Journal, 2022)
In the course of dynamic changes of educational processes, a necessity to ground on different theories to reveal valuable insights based on the analysis of the process of teaching and learning appears. In terms of the process of teaching and learning, as a process of rendering/ accepting objective knowledge, the principle of positivism in scientific research is still deeply rooted. Such approach fails to match a rapid change of the contemporary society. As an alternative to the positivist approach, interpretive social science is being created. Its essence lies in treating the process of teaching and learning as the social world which ought to be perceived from the inside and not explained from the outside. Representatives of postmodernism recognise that this shift of our society encourages exactly the constructionist thinking. The present literature review reveals the manifestation of social constructionism in the processes of teaching and learning, which highlights an intersubjective, dialogical and dialectical character of experience. The approach of social constructionism recognises a multi-variant and situation-dependent existence defined in a specific time and context; therefore, social match, discursive psychology, knowledge construction which takes place in social interaction, processes of co-creation of social reality, the role of discourse when constructing knowledge, understanding of phenomena and human existence formed through social exchanges are emphasised in the process of teaching and learning.